A pectin-based composite film based on cotton stalk powder component modification, a preparation method and application thereof

By separating cotton stalk powder components using eutectic solvents and high-pressure homogeneous microfluidic technology, lignin-curcumin nanocomposites were prepared and combined with pectin. This solved the problems of plastic film pollution and cotton stalk waste utilization, improved the mechanical properties and antibacterial and antioxidant capabilities of the pectin film, and extended the shelf life of fruits.

CN123042385APending Publication Date: 2026-11-06SHANDONG AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610760967.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing plastic film packaging materials cause white pollution, and cotton stalk waste is not effectively utilized, resulting in resource waste and environmental pollution.

Method used

The components of cotton stalk powder were separated by a eutectic solvent and combined with high-pressure homogeneous microfluidic technology to prepare lignin-curcumin nanocomposites and cationic cellulose. These were then combined with pectin to form a pectin-based composite film, which enhanced its properties through electrostatic interactions and hydrogen bond networks.

Benefits of technology

It improves the mechanical properties, antioxidant and antibacterial capabilities of pectin films, extends the shelf life of fruits, realizes the resource utilization of agricultural waste, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123042385A_ABST
    Figure CN123042385A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of food packaging materials, specifically relating to a pectin-based composite film modified from cotton stalk powder components, its preparation method, and its application. The steps are as follows: 1) The cotton stalk powder components are fractionally separated using a eutectic solvent system to efficiently separate lignin, cellulose, and other substances; 2) High-pressure homogenization microfluidic technology is introduced to assemble the extracted lignin with active polyphenol curcumin to obtain a lignin-curcumin nanocomposite material dispersion; 3) A cationic cotton stalk cellulose solution is obtained through microfluidic technology and an etherification reaction process; 4) The composite material dispersion and the cationic cotton stalk cellulose solution are mixed with a pectin aqueous solution, respectively, and after high-pressure homogenization using microfluidic technology, degassed, spread out, and naturally air-dried or oven-dried to obtain the composite film. The composite film possesses high mechanical properties, gas barrier characteristics, antioxidant and antibacterial properties, and other multifunctionalities, and can be considered a bio-based plastic with great potential to replace petrochemical plastics used in food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of food packaging materials, specifically relating to a pectin-based composite film modified from cotton stalk powder, its preparation method, and its application. Background Technology

[0002] Fruits are beloved by consumers for their appealing colors, fragrant aromas, and rich nutritional content. However, they are highly susceptible to fungal and bacterial infections during harvesting, sorting, and transportation, often resulting in high post-harvest spoilage rates. Polyvinyl chloride (PVC) and other plastic films are widely used for fruit packaging to delay ripening, maintain product appearance, and reduce losses during distribution. However, this type of non-degradable plastic waste causes serious white pollution, posing a continuous threat to soil and aquatic ecosystems. Therefore, the development of edible or biodegradable packaging materials based on biomass resources has become a global focus.

[0003] Cotton is a major economic crop globally and in my country, ranking among the world's top in both planting area and yield. However, while the cotton industry brings enormous economic benefits, it also generates a large amount of cotton stalk waste after harvest. For a long time, limited by processing costs and technological bottlenecks, the vast majority of cotton stalks have been burned directly on-site as cheap fuel or simply discarded in fields to decompose naturally. This not only causes serious carbon emissions and air pollution problems but also represents a huge waste of valuable biomass resources. Cotton stalks are a major byproduct of the cotton industry, containing over 80% lignocellulose in their dry weight, making them an important source of natural polymers. However, cotton stalks are tightly cross-linked by cellulose, hemicellulose, and lignin through physical entanglement, hydrogen bonds, and lignin-carbohydrate complex covalent bonds, forming a highly dense structure. This stable physicochemical combination limits the development and utilization of cotton stalks, resulting in a waste of biomass resources. Therefore, developing mild and efficient separation and extraction strategies to achieve in-situ separation and functional regeneration of all components of cotton stalks is key to increasing the added value of agricultural and forestry waste.

[0004] Among numerous biomass fractionation strategies, eutectic solvents exhibit superior solubility selectivity due to their unique interaction between hydrogen bond acceptors and donors. This invention reveals that, compared to traditional organic solvents or ionic liquids, an acidic system composed of lactic acid / choline chloride can drive the breaking of aryl ether bonds in the lignin structure through proton catalysis. This allows for efficient lignin extraction while maximizing the preservation of phenolic hydroxyl activity, resulting in highly chemically active lignin fragments. Furthermore, this system effectively maintains the structural integrity of the cellulose skeleton, providing a high-quality raw material base for subsequent cellulose modification. This highly efficient fractionation capability makes eutectic solvent systems an ideal medium for the high-value development of all components from cotton stalks. Summary of the Invention

[0005] This invention focuses on the full utilization of cotton stalk biomass, achieving component separation of cotton stalk powder in a DES system. Differential functionalization strategies are employed for the separated key components, and high-pressure homogenized microfluidic technology is introduced to enhance the dispersion stability of functional units in the pectin matrix, synergistically improving the light-shielding, antioxidant, and broad-spectrum antibacterial properties of the composite membrane. Furthermore, by utilizing the strong electrostatic attraction between cationic cellulose and negatively charged pectin molecules, a high-performance reinforced pectin composite membrane is developed.

[0006] In a first aspect, the present invention provides a pectin-based composite film modified from cotton stalk powder components. The pectin-based composite film is prepared by graded utilization of cotton stalk components and through electrostatic interaction and hydrogen bond network. The pectin-based composite film includes an LC-NCs composite film (LC / P film) prepared by mixing a lignin-curcumin nanocomposite material LC-NCs dispersion with a pectin aqueous solution, and a QAC / P composite film prepared by mixing a cationized cellulose solution QAC with a pectin aqueous solution. The contact angle of the LC / P film is maintained above 60°. The tensile strength of both the LC / P film and the QAC composite film is above 45 MPa. The gas barrier capacity is increased by 100%, and the antibacterial effect can reach above 95%.

[0007] Secondly, the present invention provides a method for preparing a pectin-based composite film modified with cotton stalk powder, the method comprising the following steps: 1) The eutectic solvent DES was prepared by heating and stirring, and then sealed and stored for later use; 2) Place cotton stalk powder in a dry beaker, add the eutectic solvent obtained in step 1), stir magnetically and heat, centrifuge the resulting mixed solution while hot to obtain supernatant and bottom solid residue. The supernatant is lignin-DES solution, sealed and stored for later use. The bottom solid residue is washed with anhydrous ethanol and deionized water, dried and pulverized to obtain solid powder for later use. 3) Add curcumin to the supernatant obtained in step 2) and heat and stir to dissolve. While stirring, add deionized water dropwise to the solution. After centrifugation and washing, redisperse in deionized water. After microfluidic treatment, obtain lignin-curcumin nanocomposite LC-NCs dispersion. 4) Add the solid powder obtained in step 2) to the sodium chlorite solution, heat and stir at a constant temperature, wash by centrifugation, and redisperse in deionized water. After ultrasonic, microfluidic and centrifugal treatment, bleached nanocellulose is obtained. 5) Disperse the bleached nanocellulose obtained in step 4) in an alkaline aqueous solution, add the cationic modifier dropwise while maintaining the alkaline conditions of the solution, react at a constant temperature, then adjust the pH value to neutral to terminate the reaction, centrifuge to obtain the precipitate and wash it alternately with anhydrous ethanol and deionized water, dialyze, and finally obtain a uniform and stable cationic cellulose solution QAC. 6) Mix the LC-NCs dispersion and QAC solution obtained in steps 3) and 5) with pectin aqueous solution respectively, stir continuously, add glycerol and stir again to obtain LC / P film solution and QAC / P composite film solution; 7) Spread the LC / P thin film liquid and QAC / P composite film liquid obtained in step 6) onto two glass plates respectively, dry them or let them air dry, and then peel off the films to obtain the LC / P thin film and QAC / P composite film.

[0008] Further, in step 1), the method for preparing the eutectic solvent system is as follows: choline chloride and lactic acid are added to a dry beaker to obtain a mixture, and the mixture is placed in an oil bath at 80°C and magnetically stirred at 80°C until the solid particles completely disappear, wherein the molar ratio of choline chloride and lactic acid is 1:1-1:6.

[0009] Furthermore, in step 2), the solid-liquid ratio of cotton stalk powder to eutectic solvent is 1:20, the reaction temperature is 130℃, the stirring rate is 150-500 rpm, and the reaction time is 6 h. The centrifugation rate is 8000 rpm for 5 min, and the solid residue is washed until neutral.

[0010] Furthermore, in step 3), the mass ratio of lignin to curcumin is 20:0-0:20, dispersed in 100.0 mL of deionized water, and the high-pressure microfluidic homogenizer is set to an operating pressure of 150 MPa and circulated three times.

[0011] Further, in step 4), weigh 25.0-30.0g of sodium chlorite and dissolve it in 300.0-600mL of deionized water, add 5.0g of the solid powder from step 2), adjust the pH of the system to 4-6 with glacial acetic acid, react at 90℃ for 3 h, centrifuge at 8000-10000 rpm for 4-6 min, ensure the pH is neutral after washing, use an ultrasonic cell disruptor at 60-80% power for 5-8 min, and cycle the mixture 2-5 times under 150-200 MPa pressure using a high-pressure microfluidic homogenizer.

[0012] Further, in step 5), the 5.0 g of bleached nanocellulose obtained in step 4) is dispersed in 250.0 mL of sodium hydroxide solution with a mass concentration of 0.015-0.02 g / mL, the cationic modifier is 50.0 mL of 3-chloro-2-hydroxypropyltrimethylammonium chloride solution, the pH of the system is above 10-13, the reaction is carried out continuously at 80℃ for 10-15 h, the centrifugation rate is 8000-10000 rpm for 10-15 min, and dialysis is required for 3 days.

[0013] Further, in step 6), the pectin in the pectin aqueous solution has a pectin mass-volume percentage of 2.0%, the amount of glycerol added is 30% of the pectin mass, the mass of solids in the added LC-NCs dispersion is 0.5%-5.0% of the pectin mass, the amount of cationic cellulose solution added is 0-20.0 mL at a concentration of 50.0 mg / mL, the mixture is stirred for 12 h after adding pectin, and stirred for 1 h after adding glycerol.

[0014] Furthermore, in step 7), the slurry is spread evenly onto the substrate, the substrate size is 25cm×15cm, and the thickness of the slurry is 0.3-0.5cm; the drying conditions are drying at 25-45℃ or natural drying.

[0015] Thirdly, the present invention provides the application of pectin-based composite films modified from cotton stalk powder components in food packaging.

[0016] In this invention, fractional separation of cotton stalk biomass components was achieved using a eutectic solvent (DES). The separated lignin was then combined with curcumin to successfully prepare lignin-curcumin nanocomposite materials (LC-NCs). Experimental results showed that LC-NCs retained the UV resistance properties of lignin, achieving near 100.0% blocking rates for UVA, UVB, and UAC. Furthermore, they exhibited a significant synergistic antioxidant effect with curcumin, increasing DPPH radical scavenging rate by approximately 14 times, providing highly efficient active centers for the pectin film. Simultaneously, the introduction of LC-NCs optimized the film's microstructure and density, enhancing its mechanical properties and water vapor barrier capacity. In strawberry preservation experiments, LC-NCs demonstrated excellent physiological metabolic inhibition effects, significantly extending the strawberry's shelf life. Furthermore, the cellulose separated from cotton stalks was successfully cationic modified. The modified cationic cellulose, utilizing its surface quaternized cationic groups, formed a dense electrostatic interaction and hydrogen bond network with the carboxyl groups of the pectin molecular chain, significantly improving the tensile strength (up to 47.39 MPa) and tensile strength (up to 7.95%) of the film, and imparting antioxidant and antibacterial properties to the pectin. Therefore, this invention can improve the shortcomings of pectin films to meet the requirements of food packaging applications.

[0017] The present invention has the following beneficial effects (1) Using agricultural waste cotton stalks to extract lignin and cellulose realizes the resource utilization of waste and also provides a practical solution to plastic pollution; (2) The resulting membrane has high mechanical properties and low water vapor permeability; (3) The resulting film has anti-ultraviolet, anti-oxidation and antibacterial properties (inhibits bacterial growth), and when used for packaging fruit, it can significantly extend the shelf life and maintain the quality of the fruit. Attached Figure Description

[0018] Figure 1 The graph shows the trends of solid residue rate (SR), lignin recovery rate (RL), and solid degradation rate (SD) under different DES ratios for Examples 1 and Comparative Examples 1-5.

[0019] Figure 2 Images showing the physical scale and distribution uniformity of Examples 1-7 and Comparative Examples 6-11 in an aqueous system.

[0020] Figure 3 These are macroscopic stability images of Examples 1-7 and Comparative Examples 6-11.

[0021] Figure 4 The infrared spectra of the composite films of Examples 1-6 and Comparative Example 13 are shown.

[0022] Figure 5 The images show the ultraviolet spectra of Examples 1-6 and Comparative Example 13.

[0023] Figure 6 a is a water contact angle diagram of Examples 1-6 and Comparative Example 13; Figure 6 b is a water vapor transmission rate diagram of Examples 1-6 and Comparative Example 13; Figure 6 c represents the stress-strain curves of Examples 1-6 and Comparative Example 13; Figure 6 d represents the trend of TS and EAB as a function of component ratio in Examples 1-6 and Comparative Example 13.

[0024] Figure 7 The image shows the antibacterial properties of the composite membrane assembly in Example 2 and Comparative Example 13.

[0025] Figure 8 a is the infrared spectrum of Examples 1, 7-9 and Comparative Example 13; Figure 8 b shows the XRD patterns of Examples 1, 7-9 and Comparative Example 13.

[0026] Figure 9 The thermal stability diagrams are for Examples 1, 7-9 and Comparative Example 13.

[0027] Figure 10 The diagrams show the water contact angles of Examples 1, 7-9, and Comparative Example 13.

[0028] Figure 11 The images show the ultraviolet spectra of Examples 1, 7-9 and Comparative Example 13.

[0029] Figure 12 The stress-strain curves are for Examples 1, 7-9 and Comparative Example 13.

[0030] Figure 13 Images showing the water vapor transmission rate and oxygen transmission rate of Examples 1, 7-9 and Comparative Example 13.

[0031] Figure 14 Images showing the DPPH free radical scavenging rate and total antioxidant capacity of Examples 1, 7-9 and Comparative Example 13.

[0032] Figure 15 The antibacterial efficacy of Examples 1, 7-9 and Comparative Example 13 is shown.

[0033] Figure 16 The color changes of Examples 1, 7-9 and Comparative Example 13 under different pH conditions are shown.

[0034] Figure 17 The preservation effect of using polyethylene preservation film, the composite film of Examples 1, 7-9 and Comparative Example 13, on strawberries stored at room temperature for 6 days was measured.

[0035] Figure 18 The weight loss rate of strawberries using composite films made of polyethylene cling film, Examples 1, 7-9 and Comparative Example 13.

[0036] Figure 19 a represents the change in strawberry firmness when using polyethylene plastic wrap, Examples 1, 7-9 and Comparative Example 13; Figure 19 b represents the change in the soluble solids content of strawberries; Figure 19 c represents the change in the total bacterial count of strawberry fruit coated on a plate; Figure 19 def represents the color variation of the strawberry.

[0037] Figure 20 Images showing biosafety verification of Examples 1, 7-9 and Comparative Example 13.

[0038] Figure 21 a represents the ATR-FTIR spectrum of the composite films of Examples 1, 10-12 and Comparative Example 13; Figure 21 b shows the XRD diffraction patterns of Examples 1, 10-12 and Comparative Example 13.

[0039] Figure 22 a represents the ultraviolet spectra of Examples 1, 10-12, and Comparative Example 13; Figure 22 b represents the effect of TS and EBA on Examples 1, 10-12 and Comparative Example 13. Figure 22 c and d represent the OP and WVP of Examples 1, 10-12 and Comparative Example 13, respectively.

[0040] Figure 23 The diagrams show the water contact angles of Examples 1, 10-12 and Comparative Example 13.

[0041] Figure 24 The antibacterial efficacy of Examples 1, 10-12 and Comparative Example 13 is shown.

[0042] Figure 25 Changes in the appearance of strawberries stored in plastic wrap, Examples 1, 10-12 and Comparative Example 13.

[0043] Figure 26 The weight loss rate of strawberries in the following examples: plastic wrap, Examples 1, 10-12 and Comparative Example 13.

[0044] Figure 27 a represents the change in strawberry firmness when using polyethylene plastic wrap, Examples 1, 7-9 and Comparative Example 13; Figure 27 b represents the change in the soluble solids content of strawberries; Figure 27 c represents the change in the total bacterial count of strawberry fruit coated on a plate; Figure 27 def represents the color variation of the strawberry.

[0045] Figure 28 The appearance, chromaticity values ​​(L*, a*, b*), total color difference (∆E*), haze, and transparency of Examples 1, 7-9, and Comparative Example 13 are compared.

[0046] Figure 29 The appearance, chromaticity values ​​(L*, a*, b*), total color difference (∆E*), haze, and transparency of Examples 1, 10-12, and Comparative Example 13 are compared. Detailed Implementation

[0047] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to examples. It should be noted that the following examples are only for further illustrating the present invention, and the embodiments of the present invention are not limited thereto. Some non-essential adjustments and improvements made by those skilled in the art based on the above-described inventive solutions still fall within the protection scope of the present invention.

[0048] Example 1

[0049] 1) Add choline chloride and lactic acid in a 1:5 molar ratio to a dry beaker, place it in an oil bath at 80°C, and stir magnetically at 80°C until the solid particles completely disappear, forming a uniform, transparent and non-crystallized oily liquid, namely DES. Seal and store for later use. 2) Place a certain mass of cotton stalk powder in a dry beaker, and add the eutectic solvent DES obtained in step 1) at a solid-liquid ratio of 1:20 (mass ratio, cotton stalk powder: DES). Stir magnetically at 130℃ for 6 h. After the reaction is complete, centrifuge the mixture while it is hot (8000 rpm, 5 min) to obtain the supernatant and the bottom solid residue. Seal and store the lignin-DES supernatant obtained by centrifugation for later use. Wash the bottom solid residue with anhydrous ethanol and deionized water until neutral, dry and pulverize to obtain solid powder for later use. The purpose of this step is to separate the lignin-containing DES supernatant from the cellulose precipitate by physical means. 3) Weigh a certain amount of curcumin and add it to the lignin-DES solution at a mass ratio of lignin:curcumin of 20:8. Dissolve the curcumin by stirring at 60°C. While stirring at high speed, add 20.0 mL of deionized water dropwise to form a preliminary nano-aggregate suspension. Centrifuge and wash the preliminary nano-aggregate suspension three times with deionized water to obtain a solid precipitate to remove residual DES. Then dissolve the solid precipitate in 100.0 mL of deionized water and transfer it to a high-pressure microfluidic homogenizer. Set the operating pressure (150-200 MPa) and cycle 2-5 times to obtain a lignin-curcumin nanocomposite material (LC-NCs) dispersion with high stability and uniform particle size distribution. 4) Weigh 25.0 g of sodium chlorite (NaClO2) and dissolve it in 500.0 mL of deionized water. Adjust the pH of the system to 4.6 precisely using glacial acetic acid. Add 5.0 g of the solid powder from step 2), and react at 90℃ for 3 h. After the reaction, centrifuge (10000 rpm, 6 min) and repeatedly wash the sodium chlorite (reacted at 90℃ for 3 h) until neutral to obtain bleached cellulose solid. Redisperse the obtained bleached cellulose solid in deionized water and perform preliminary dispersion using an ultrasonic cell disruptor (60-80% power, 5-10 min). Subsequently, circulate the suspension through the ultrasonic cell disruptor at 150-200 MPa pressure 2-5 times. Nanoparticle exfoliation of cellulose is achieved through ultra-high shear force. Finally, collect the bleached nanocellulose by centrifugation. 5) First, prepare 250.0 mL of sodium hydroxide (NaOH) solution with a mass concentration of 0.015 g / mL. Disperse 5.0 g of the bleached cellulose obtained in step 4) in the solution and stir to fully swell and activate the cellulose. Then, add 50.0 mL of cationic modifier (3-chloro-2-hydroxypropyltrimethylammonium chloride solution) dropwise to the system. Maintain the pH of the system above 11 using 5.0% NaOH solution and react continuously at 80℃ for 10 h. After the reaction is complete, adjust the pH of the solution to neutral (pH=7) using glacial acetic acid to terminate the reaction. Centrifuge the mixture (8000 rpm, 10 min) and wash it three times alternately with anhydrous ethanol and deionized water to remove unreacted modifier and byproducts. Finally, place the product in a dialysis bag and dialyze it with deionized water for 3 days. Finally, obtain 100.0 mL of homogeneous and stable cationic cellulose solution, abbreviated as QAC, and store it at 4℃ in the dark. 6) Add LC-NCs at a loading of 2.5% (w / w relative to pectin mass) to 100.0 mL of deionized water, and transfer the solution to a high-pressure microfluidic homogenizer. Circulate the solution three times to dissolve 2.0 g of pectin in the solution. Stir continuously for 12 h to ensure complete dissolution of the pectin. Add 30% (by weight of pectin) of glycerol as a plasticizer and stir for 1 h. Take 4.0 mL of a 50.0 mg / mL QAC solution and place it in a 200.0 mL beaker. Dilute to 100.0 mL with deionized water and stir until the QAC is evenly dispersed. Dissolve 2.0 g of pectin in the above solution and stir continuously for 12 h to ensure complete dissolution. Add 30% (by weight of pectin) of glycerol as a plasticizer and stir for 1 h.

[0050] 7) The two film-forming solutions were cast onto 15 cm × 25 cm acrylic plates and dried in an oven at 40 °C for 12 h to obtain LC / P film and QAC / P composite film.

[0051] Example 2 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin is 20:0, while all other aspects are the same as in Example 1.

[0052] Example 3 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin is 20:1, while all other aspects are the same as in Example 1.

[0053] Example 4 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin is 20:5, while all other aspects are the same as in Example 1.

[0054] Example 5 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin is 20:12, while all other aspects are the same as in Example 1.

[0055] Example 6 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin is 0:20, while all other aspects are the same as in Example 1.

[0056] Example 7 The difference from Example 1 is that in step 6), LC-NCs are mixed with pectin at a concentration of 0.5% (w / w relative to the pectin mass), while all other aspects are the same as in Example 1.

[0057] Example 8 The difference from Example 1 is that in step 6), LC-NCs are mixed with pectin at a concentration of 1.5% (w / w relative to the pectin mass), while all other aspects are the same as in Example 1.

[0058] Example 9 The difference from Example 1 is that in step 6), LC-NCs are mixed with pectin at a concentration of 5% (w / w relative to the pectin mass), while all other aspects are the same as in Example 1.

[0059] Example 10 The difference from Example 1 is that in step 6), 0.4 mL of 50.0 mg / mL QAC solution was placed in a 200.0 mL beaker, and everything else was the same as in Example 1.

[0060] Example 11 The difference from Example 1 is that in step 6), 12.0 mL of 50.0 mg / mL QAC solution was placed in a 200.0 mL beaker, and everything else was the same as in Example 1.

[0061] Example 12 The difference from Example 1 is that in step 6), 20.0 mL of 50.0 mg / mL QAC solution was placed in a 200.0 mL beaker, and everything else was the same as in Example 1.

[0062] Comparative Example 1 The difference from Example 1 is that choline chloride and lactic acid were heated in a 1:1 molar ratio, and only the reaction with cotton stalk powder was carried out; no subsequent experiments were conducted.

[0063] Comparative Example 2 The difference from Example 1 is that choline chloride and lactic acid were heated in a 1:2 molar ratio, and only the reaction with cotton stalk powder was carried out; no subsequent experiments were conducted.

[0064] Comparative Example 3 The difference from Example 1 is that choline chloride and lactic acid were heated in a 1:3 molar ratio, and only the reaction with cotton stalk powder was carried out; no subsequent experiments were conducted.

[0065] Comparative Example 4 The difference from Example 1 is that choline chloride and lactic acid were heated in a molar ratio of 1:4, and only the reaction with cotton stalk powder was carried out; no subsequent experiments were conducted.

[0066] Comparative Example 5 The difference from Example 1 is that choline chloride and lactic acid were heated in a molar ratio of 1:6, and only the reaction with cotton stalk powder was carried out; no subsequent experiments were conducted.

[0067] Comparative Example 6 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:0, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0068] Comparative Example 7 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:1, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0069] Comparative Example 8 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:5, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0070] Comparative Example 9 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:8, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0071] Comparative Example 10 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:12, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0072] Comparative Example 11 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 0:20, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0073] Comparative Example 12 The difference from Example 1 is that in step 3), the mass ratio of lignin to curcumin was 20:0, and no microfluidic treatment was performed. Only experiments were conducted on the separation of cotton stalk powder components and the synthesis of lignin-curcumin nanocomposite material (LC-NCs) dispersion to determine its stability. No subsequent experiments were performed.

[0074] Comparative Example 13 Pectin powder was dissolved in deionized water to prepare a pectin aqueous solution (2%, w / v) (all the above pectin aqueous solutions were prepared by the same method). The solution was stirred overnight to obtain a film-forming solution and degassed. The film-forming solution was poured onto an acrylic plate with a substrate size of 25cm × 15cm and a slurry thickness of 0.4cm. The film was naturally dried at room temperature and then peeled off to obtain a composite film. The prepared composite film has low mechanical properties and poor antioxidant capacity and antibacterial activity.

[0075] By using lactic acid / choline chloride eutectic solvents (DES) to treat cotton stalk powder, selective disintegration of components can be achieved. Figure 1The trends of solid residue rate (SR), lignin recovery rate (RL), and solid degradation rate (SD) under different DES ratios are shown in Examples 1 and Comparative Examples 1-5. With increasing lactic acid ratio, lignin recovery initially increased and then decreased. RL reached its maximum value of 16.6% when the molar ratio of choline chloride to lactic acid was 1:5, indicating that the DES at this ratio caused the most thorough destruction of the lignin-carbohydrate complex, providing an active precursor for the subsequent preparation of lignin-curcumin nanocomposites. In contrast, the solid residue rate (SR) and solid degradation rate (SD) did not show a clear trend with changes in the EDS ratio, but fluctuated within a certain range. At a 1:5 ratio, SR remained at 26.8%, and high-quality cellulose could be obtained through subsequent bleaching. Therefore, this invention considers the molar ratio (1:5) at which RL reaches its maximum value as the optimal separation condition, achieving efficient recovery of liquid-phase lignin for the construction of LC-NCs while retaining solid residue for QAC preparation, successfully realizing the graded and high-value utilization of cotton stalk components.

[0076] To determine the physical scale and distribution uniformity of LC-NCs at different proportions in an aqueous system, a nanoparticle size potentiometric analyzer was used for characterization: An appropriate amount of LC-NCs nanocomposite material was weighed and added to deionized water to prepare a suspension with a mass concentration of 0.1 mg / mL. After ultrasonic treatment for 5-10 min, approximately 1.5 mL of the dispersion was placed in a standard cuvette, and its intensity distribution was measured using a nanoparticle size analyzer. Figure 2 As shown in Examples 1-7 and Comparative Examples 6-11, the initial particle size of LC was large and the distribution was uneven. After HPH processing, the particle size of LC-NCs of all mass ratios was in the range of 50-500 nm.

[0077] The stability of the system after 20 days at room temperature was visually recorded using optical photographs, showing changes in the system's appearance. The macroscopic stability results were highly correlated with the microscopic particle size data. For example... Figure 3 As shown in Examples 1-7 and Comparative Examples 6-11, the stability of the untreated groups exhibited a clear ratio-dependent effect. At higher Lignin content (e.g., 20:1, 20:5), no significant precipitation was observed. However, with increasing Cur content (e.g., 20:8, 20:12) and in the pure Cur group, severe particle aggregation occurred, leading to significant gravitational sedimentation within 20 days. The HPH-treated LC-NCs groups (except for the pure Cur group which still showed trace precipitation) maintained good kinetic stability during the 20-day storage period, with homogeneous solutions and no visible precipitation. This indicates that HPH not only refined the particle size but also promoted the co-assembly of Lignin and Cur. The complex branched structure of Lignin molecules provides a significant steric hindrance effect for the nanocomposite materials, effectively suppressing particle collision and aggregation, thereby ensuring the long-term kinetic stability of the LC-NCs system.

[0078] The chemical structure and molecular bonding of the materials were analyzed using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). The wavenumber range was 4000–400 cm⁻¹, the spectral resolution was 4 cm⁻¹, and 32 scans were performed (background scan and subtraction were performed before measurement). LC-NCs composite films with different mass ratios were characterized by ATR-FTIR. The results are as follows: Figure 4 As shown, the infrared spectra of the composite films from Examples 1-6 and Comparative Example 13 exhibit high similarity, with no new absorption peaks appearing. This indicates that LC-NCs are primarily bonded to the pectin matrix through non-covalent interactions (such as hydrogen bonds and van der Waals forces). This ensures the integrity of the active functional groups of Cur and Lignin, which is beneficial for their antioxidant and antibacterial functions. Simultaneously, it demonstrates that LC-NCs have good compatibility in the pectin matrix, and the nanocomposite material can be uniformly embedded in the pectin molecular chain network without disrupting the original molecular structure of the matrix.

[0079] To evaluate the functional stability of the composite film under illumination, this study irradiated the composite film under a xenon lamp for 4 hours and compared the changes in ultraviolet-visible light transmittance of the composite film before and after irradiation. Figure 5 As shown in Examples 1-6 and Comparative Example 13, the transmittance of the composite film loaded with LC-NCs significantly decreased in the ultraviolet region (200-400 nm). This is mainly attributed to the unique phenolic hydroxyl groups and chromophores in the Lignin structure, as well as the UV absorption effect of the abundant conjugated double bond system of Cur. When the mass ratio of Lignin to Cur reaches 20:8 and 20:12, the composite film can almost completely block the UVA, UVB, and UVC bands, providing an ideal physical barrier for photosensitive foods. After 4 hours of strong light irradiation, the shielding curve of the pure Lignin pectin film remained basically unchanged, while the UV blocking ability of the film containing pure Cur pectin showed a significant decrease in the region above 300 nm, indicating that Cur molecules are highly susceptible to photo-oxidative degradation under UV light. Experiments showed that the photostability of the composite film decreased more significantly when the Cur ratio was low. This may be because a small amount of Cur molecules are rapidly consumed when resisting photo-oxidation. As the proportion of Curl increases, there is more Curl in the system to continuously exert its antioxidant effect. In addition, the high concentration of Curl can also absorb ultraviolet rays and play an effective light shielding role, blocking light from penetrating into the interior of the film, thereby ensuring the composite material's long-lasting and stable UV protection function.

[0080] Water contact angle (WCA) is an important indicator for evaluating the hydrophobic properties of membrane surfaces. Figure 6As shown in Figure a, the WCA of the composite membranes in Examples 1-6 and Comparative Example 13 was higher than that of the pure pectin membrane. The WCA of the composite membrane loaded with pure Lignin (20:0) was slightly higher than that of the pure pectin membrane. As the Lignin / Cur ratio increased from 20:1 to 20:8, the WCA of the composite membrane remained relatively stable without significant fluctuations, while the WCA of the membrane loaded with pure Cur showed the most significant increase. This is mainly attributed to the strong inherent hydrophobicity of Cur molecules and the possible surface enrichment phenomenon in the pectin matrix.

[0081] Figure 6 As shown in b, the water vapor transmission rate (WVP) of the composite membranes in Examples 1-6 and Comparative Example 13 exhibits a pattern of first decreasing and then increasing. This is mainly because, with the appropriate addition of Cur, Cur forms a tight cross-linked network with Lignin and the pectin matrix through non-covalent interactions such as hydrogen bonding and π-π stacking, increasing the internal density of the film and thus effectively reducing WVP. However, when the Cur ratio is too high, excessive Cur easily forms coarse, irregular aggregates or crystals during film formation. This local self-aggregation not only disrupts the original continuity of the polymer matrix but also leads to interfacial gaps in the internal structure of the membrane, providing channels for water vapor diffusion, causing WVP to rebound. In summary, the composite membrane loaded with LC-NCs (20:8) achieves the optimal balance between intermolecular interactions and structural density.

[0082] Mechanical properties are key indicators for evaluating the structural integrity and practical application potential of packaging materials. Figure 6 c shows the stress-strain curves of the LC-NCs composite films of Examples 1-6 and Comparative Example 13. Figure 6 Figure d reflects the trend of TS and EAB as the component ratio changes. From loading pure lignin (20:0) to composite LC-NCs (20:8), TS remained at a relatively high level overall. This indicates that LC-NCs played an effective nano-reinforcing role in the pectin matrix. Since both lignin and cur contain abundant active groups such as phenolic hydroxyl groups in their structures, they can form a dense intermolecular hydrogen bond network with pectin. Compared with the relatively stable TS, EAB was significantly increased at the LC-NCs (20:8) ratio. This is mainly because at this ratio, the co-assembly of lignin and cur reached the optimal state, forming morphologically regular and uniformly dispersed nanoparticles. These uniformly dispersed nanounits can form good interfacial compatibility with the film-forming matrix, thereby improving the flexibility of the composite film. When the cur ratio continued to increase (20:12) or completely replaced lignin (0:20), both TS and EAB decreased. This is because the excess cur caused the nanoparticles to aggregate.

[0083] The antimicrobial properties of active packaging materials are crucial for extending the shelf life of food. This study used colony counting to evaluate the inhibitory effects of LC-NCs with different Lignin / Cur ratios on Staphylococcus aureus and Escherichia coli. Figure 7 As shown, the composite film group of Example 2 showed no significant difference from that of Comparative Example 13, indicating that the antibacterial ability of a single lignin component is limited. With the increase of the proportion of Cur in LC-NCs, the antibacterial ability gradually increased, and the inhibition rate significantly improved when the proportion reached 20:8 or higher. This demonstrates that Cur is the main active source for the bactericidal function of the active packaging film, and the active groups in its molecules can induce oxidative stress in bacteria, leading to bacterial inactivation by disrupting the cell membrane potential.

[0084] The structure of pectin composite membranes with different LC-NCs contents was characterized by ATR-FTIR and XRD. Figure 8 a shows the infrared spectra of Examples 1, 7-9, and Comparative Example 13. Comparative Example 13 exhibits a broad -OH stretching vibration peak near 3305 cm⁻¹, with characteristic absorption peaks at 1739 cm⁻¹ and 1605 cm⁻¹ corresponding to the esterified carbonyl group (C=O) and the free carboxyl group (-COO⁻), respectively. The main characteristic peaks of the composite film did not shift significantly after the introduction of LC-NCs, indicating that the interaction between LC-NCs and the pectin matrix is ​​mainly physical filling and hydrogen bonding, without forming strong covalent bonds, effectively preserving the original functional active centers (such as polyphenolic hydroxyl groups) of lignin and curcumin. Figure 8 b is the XRD pattern. Comparative Example 13 shows a broad, diffuse peak at approximately 20° 2θ, exhibiting a typical amorphous structure. After the addition of LC-NCs, the composite membrane maintained this amorphous profile. This good physical compatibility corroborates the ATR-FTIR results, indicating that LC-NCs exist stably in the composite system at the nanoscale, laying the structural foundation for improving the physical barrier properties of the membrane.

[0085] The effect of LC-NCs addition on the thermal stability of pectin composite films was evaluated using TGA and DTG. Figure 9As shown, the initial weight loss of all films between 30℃ and 150℃ is mainly attributed to the evaporation of bound water within the membrane and the loss of some adsorbed water. Weight loss in the range of 150℃ to 280℃ is due to the thermal degradation of glycerol added during film preparation. The subsequent major weight loss phase occurs between 280℃ and 400℃, primarily related to the depolymerization and thermal decomposition of pectin macromolecular chains. Experimental results indicate that although the introduction of LC-NCs did not significantly affect the maximum decomposition temperature of the pectin film, the residual weight of the composite film in this stage and the final stage (800℃) was slightly higher than that of the pure pectin film. This suggests that the addition of LC-NCs enhances the thermal stability of the pectin composite film to some extent, giving it better structure retention under high-temperature conditions.

[0086] Contact angle (WCA) is an important indicator for evaluating the hydrophobicity and water resistance stability of food packaging materials. Figure 10 This study demonstrates the dynamic evolution of water droplet contact angles in pectin composite films with different LC-NCs contents from 0 to 300 s. The results show that the contact angle of the pure pectin film at 0 s is 64.89°. With increasing LC-NCs content, the initial contact angle of the composite film shows a significant upward trend, reaching 78.94° for the 5.0% LC / P composite film. This is mainly because the curcumin and lignin components in LC-NCs have better natural hydrophobicity compared to the highly hydrophilic pectin matrix. At 300 s, the contact angle of the pure pectin film is only 51.64°, while the composite films with more than 1.5% LC-NCs maintain a contact angle above 60°. This indicates that the introduction of LC-NCs improves the strong hydrophilicity of the pectin film. This improved performance helps reduce moisture penetration of active packaging materials during the storage of moist foods, thus better protecting the inner packaging contents.

[0087] The optical properties of packaging materials are one of the core dimensions for evaluating their functionality. They not only affect the appearance of the product, but also play a key role in delaying the oxidative deterioration of photosensitive foods and extending their shelf life by constructing photophysical barriers. Figure 28This study demonstrates the effects of different LC-NCs contents on the appearance, chromaticity values ​​(L*, a*, b*), total color difference (∆E*), haze, and transparency of pectin composite films. With increasing LC-NCs content, the L* of the composite film decreases, primarily because LC-NCs enhance the absorption and scattering of visible light, leading to a decrease in brightness. Both a* and b* increase, due to the combined effect of the inherent golden-yellow characteristic of curcumin in LC-NCs and the chromophores of lignin (such as phenolic hydroxyl and carbonyl groups). The introduction of LC-NCs increases the haze of the composite film and decreases its transparency, but this effectively enhances the film material's light-shielding protection function for the food inside. Although visible light transmittance decreases, the introduction of LC-NCs endows the pectin film with excellent UV shielding capabilities, such as… Figure 11 The 1.5% LC / P composite film shown can block ultraviolet light in the 200-400 nm range. This is because the aromatic ring structure in lignin molecules and the conjugated double bond system in curcumin molecules are highly efficient sources of ultraviolet absorption. This high-performance ultraviolet blocking property can effectively inhibit the photodegradation of sensitive nutrients in food.

[0088] Figure 12 The stress-strain curves of pectin composite films with different LC-NCs contents are shown. Tensile strength initially increases and then decreases with increasing LC-NCs content, reaching a maximum of 53.03 MPa when the content increases from 0% to 2.5%. This is mainly attributed to the uniform dispersion of LC-NCs in the pectin matrix and the physical cross-linking structure formed with pectin, which effectively constrains polymer chain movement, thereby enhancing tensile strength. With further increases in LC-NCs content, tensile strength decreases due to localized agglomeration caused by excessive filler. Elongation at break also shows an initial increase followed by a decrease, reaching a peak of 18.01% at a 2.5% loading. This may be because, at relatively low loadings, the moderate interaction between LC-NCs and pectin molecular chains optimizes the internal network structure of the film, improving its ductility. When the loading reaches 5.0%, EAB and TS decrease, indicating that excessive filler disrupts the continuity of the pectin network, causing the material to exhibit greater brittleness.

[0089] like Figure 13 As shown, with the increase of LC-NCs loading, the WVP and OP of the composite membrane both show a trend of first decreasing and then increasing. When the loading is 2.5%, the film exhibits the best barrier performance, mainly because the nanoparticles are well dispersed in the matrix, making the structure of the pectin composite membrane more compact and effectively blocking gas permeation. However, when the loading is further increased to 5.0%, the barrier performance decreases to some extent due to interfacial defects caused by filler aggregation.

[0090] The bioactive function of composite films is a key indicator for evaluating their use as active packaging materials. Figure 14 The effects of different LC-NCs on the DPPH radical scavenging rate and total antioxidant capacity of pectin composite films were investigated. With increasing LC-NCs doping ratio, both the DPPH scavenging capacity and total antioxidant capacity of the film showed an enhanced trend. This is because the lignin and curcumin components in LC-NCs are rich in phenolic hydroxyl groups and have a highly conjugated electron system, enabling them to act as efficient hydrogen donors or electron donors, rapidly neutralizing free radicals and thus blocking the initiation and transmission of oxidation chain reactions.

[0091] Antimicrobial properties are an important functional attribute of active packaging materials for ensuring food safety and extending shelf life. For example... Figure 15 As shown, this study selected typical Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) as model organisms to evaluate the effect of LC-NCs on the antibacterial efficacy of pectin composite membranes. The composite membrane loaded with LC-NCs exhibited significant antibacterial activity, and the antibacterial effect increased with increasing filler content. Due to the lack of active groups, bacteria grew vigorously on the agar surface of the pure pectin membrane group; however, after the addition of LC-NCs, the total bacterial count decreased significantly. This indicates that LC-NCs, through the synergistic effect of disrupting bacterial cell membrane potential and inducing oxidative stress, endow the composite membrane with excellent biological defense functions, making it an ideal material for ensuring food microbiological safety.

[0092] Figure 16 The color changes of LC-NCs materials and their composite films under different pH conditions are shown. The LC-NCs solution exhibits little color change within the pH range of 3–8, remaining relatively stable overall. However, a significant color change occurs when the pH increases from 9 to 10. This phenomenon is mainly related to the pH-responsive characteristics of curcumin molecules: curcumin molecules contain phenolic hydroxyl groups and β-diketone structures, which readily undergo deprotonation under alkaline conditions, leading to changes in the molecular conjugation system and causing a red or blue shift in the absorption peak, resulting in a noticeable color change. Under acidic or neutral conditions, the curcumin molecular structure is relatively stable, thus the color change is not significant. On the other hand, lignin, as a natural aromatic polymer, contains numerous phenolic hydroxyl groups and aromatic ring structures. Curcumin molecules form a stable composite system through intermolecular forces such as hydrogen bonding and π–π interactions. The combination of curcumin and lignin somewhat restricts changes in their molecular structure. Therefore, the color change of the LC system under different pH conditions is relatively small.

[0093] like Figure 17-19 As shown, strawberries, as a typical fruit with high respiration rate, are extremely susceptible to moisture loss and microbial infection during storage and transportation. Figure 17This study demonstrates the preservation effects of using polyethylene (PE) cling film, pure pectin film, and composite films with varying LC-NCs contents to package strawberries for 6 days at room temperature. A comparison of photos from Day 0 to Day 6 shows that, due to the extremely low gas permeability of PE cling film, its weight loss rate was the lowest (…). Figure 18 However, this resulted in a high-humidity and oxygen-deficient microenvironment inside the packaging. Combined with the lack of antibacterial properties of the PE film, this led to severe rotting and microbial growth in the strawberries. Due to the large number of hydrophilic groups in the pectin structure, its water vapor permeability was high, resulting in the fastest weight loss rate for the strawberries. Compared to polyethylene film and pure pectin film, strawberries packaged with LC / P composite film maintained a relatively plump appearance and bright red color even on the 6th day. This is mainly because the LC / P composite film has excellent antibacterial properties and superior physical barrier properties. As time progressed, the weight loss rate of all composite films showed an increasing trend, but the weight loss rate of the LC-NCs composite film group was significantly lower than that of the pure pectin film. This is because the uniform filling of LC-NCs makes the pectin structure more compact, reducing WVP and OP, thereby slowing down gas exchange between the inside and outside of the packaging and creating a relatively stable respiratory microenvironment for the strawberries.

[0094] To thoroughly evaluate the biosafety of LC / P composite films, this study used L929 mouse fibroblasts as a model and investigated their effects on cell growth viability and morphology using the CCK-8 assay. The results are as follows: Figure 20 As shown in the figure. Microscopic observation revealed that, compared with the control group, L929 cells in the LC / P composite film extract treatment group exhibited good adherent growth and uniform cell density distribution. Even in the group with the highest LC-NCs nanoparticle addition, the cells maintained their typical spindle-shaped appearance, without obvious apoptosis phenomena such as cell shrinkage, rounding, or detachment. Furthermore, CCK-8 quantitative analysis showed that the relative cell proliferation rate in each experimental group remained above 90%, with no statistically significant difference (p>0.05). These experimental results fully demonstrate that the LC / P composite film possesses excellent biocompatibility and cell safety, and has extremely low potential toxicity risk when used as a food packaging material.

[0095] like Figure 21Figure a shows the ATR-FTIR spectra of the composite films of Examples 1, 10-12, and Comparative Example 13. Comparative Example 13 exhibits typical characteristic absorption peaks at 3301 cm⁻¹, 1737 cm⁻¹, and 1601 cm⁻¹, corresponding to the stretching vibrations of hydroxyl groups (-OH), carboxyl groups (C=O), and the asymmetric stretching vibrations of free carboxyl groups (-COO-), respectively. As the QAC content increased from 1.0% to 50.0%, the characteristic peaks of pectin did not change significantly. This indicates that no new covalent bonds were formed between QAC and the pectin molecular chains, and the system was mainly bound through physical filling and electrostatic interactions. Figure 21 b shows the XRD diffraction pattern of the composite film. The pure pectin film exhibits a diffuse peak near 2θ = 13°. With increasing QAC content, the composite film shows a distinct diffraction peak at 2θ = 22.4°, corresponding to the (200) crystal plane of the cellulose type I structure. This indicates that the introduction of QAC breaks the amorphous state of pectin and successfully implants crystalline microregions with a certain degree of regularity into the composite system.

[0096] like Figure 29 Analysis of the optical parameters of the composite film revealed that the pure pectin film had a transparency of up to 89.63%. With increasing QAC content, the transmittance of the composite film decreased slightly, but remained at 86.43% at a high concentration of 50.0%, indicating that QAC formed small-sized crystalline micro-regions within the pectin matrix and was uniformly dispersed without significant optical phase separation. The haze of the film increased from 9.04 to 67.31. This high transmittance and high haze characteristic confirms strong interfacial interactions and physical embedding between QAC and pectin molecular chains. The filler constructs a dense nano-network within the matrix to enhance internal light scattering while maintaining good visual light transmission. Color difference analysis showed a decrease in the L value and an increase in the b value, resulting in a slightly yellowish hue. The total color difference ∆E* remained stable, indicating that the introduction of QAC effectively strengthened the microstructure while preserving the original appearance consistency of the pectin film.

[0097] like Figure 22 As shown in Figure a, the shielding efficiency of the composite film in the ultraviolet region (200-400 nm) increases with the increase of QAC content. Pure pectin film has weak UV blocking ability, while the UV resistance of the film is significantly enhanced after the introduction of QAC. This is attributed to two factors: firstly, the dense network structure formed by QAC nanocellulose in the pectin matrix; and secondly, the fact that QAC retains a certain crystalline structure, and its crystalline microregions reflect and absorb ultraviolet light.

[0098] Figure 22b illustrates the effect of QAC content on the tensile strength (TS) and elongation at break (EBA) of the composite film. With increasing QAC content, both TS and EBA of the composite film improved. The improved tensile strength is due to the high aspect ratio of the QAC effectively absorbing the applied stress through physical filling, while the improved elongation at break is attributed to the good interfacial adhesion achieved through electrostatic attraction and hydrogen bonding between QAC and pectin, resulting in a synergistic improvement in film strength and toughness.

[0099] Figure 22 As shown in figures c and d, the OP and WVP of the film initially decrease and then increase with the change in QAC content, with the composite film exhibiting optimal barrier performance at a QAC content of 10.0%. When the QAC content increases from 1.0% to 10.0%, the uniformly dispersed QAC forms a complex physical barrier within the pectin matrix, effectively preventing the penetration of oxygen and water molecules. With further increases in QAC content, excessively high concentrations of QAC may lead to localized aggregation. This interfacial discontinuity allows for gas permeation. Furthermore, QAC itself contains a large number of hydroxyl and quaternary ammonium groups, exhibiting a certain degree of hydrophilicity, which weakens the film's barrier effect against water molecules.

[0100] Figure 23 The figure shows the dynamic evolution of the contact angle of the composite film surface after water droplets contact the film from 0 to 300 s. As can be seen from the figure, the contact angle of the composite film improves with increasing QAC content. The contact angle of pure pectin at 0 s is 66.85°, exhibiting hydrophilicity, while the initial contact angle of the 50.0% QAC / P film reaches a maximum of 80.43°. This is mainly attributed to the fact that QAC increases the surface roughness of the film during film formation. After a 300-s wetting process, the contact angles of each component film decreased to varying degrees, but the addition of QAC significantly improved the water resistance of the pectin film.

[0101] The antibacterial effects of pure pectin membranes and QAC / P composite membranes with different QAC contents against *Escherichia coli* and *Staphylococcus aureus* were evaluated using the plate count method. Figure 24 As shown, pure pectin membranes exhibit virtually no antibacterial activity. However, the antibacterial performance of the composite membrane significantly improves with increasing QAC content. Quantitative analysis revealed that the 50.0% QAC / P composite membrane demonstrated an inhibition rate exceeding 99.0% against both tested bacteria, exhibiting superior bactericidal efficacy. This is primarily attributed to the high density of quaternary ammonium cation groups in the QAC molecular structure. The positively charged QAC attracts the negatively charged bacterial cell wall through electrostatic attraction, subsequently inserting its long alkyl chains into the cell membrane lipid bilayer. This leads to impaired cell membrane integrity, leakage of intracellular substances, and ultimately bacterial death.

[0102] By observing the changes in the appearance of food during storage, the actual effectiveness of composite films in delaying physiological deterioration of fruit can be evaluated most directly. The changes in the appearance of strawberries stored with composite films are shown below. Figure 25 As shown, strawberries in the polyethylene film and pure pectin film groups exhibited significant tissue collapse and mold growth on day 6 due to severe microbial infection and respiration. In contrast, with increasing QAC content, the cationized fiber composite film significantly inhibited mold growth through a positive charge contact sterilization mechanism, effectively maintaining the morphological integrity of the fruit. This indicates that cation modification endows the film with excellent bioprotective functions and can significantly extend the sensory life of strawberries.

[0103] To comprehensively evaluate the preservation performance of the composite film, the weight loss rate, firmness, total soluble solids (TSS), total bacterial count, and color values ​​(L*, a*, b*) of strawberries during storage were measured. Figure 26 and 27 ).Depend on Figure 26 It can be seen that during the 6-day storage period, the weight loss rate of all strawberries increased with time. Polyethylene plastic wrap had the lowest weight loss rate due to its poor air permeability, but its lack of antibacterial ability led to severe rotting and decreased firmness of the strawberries. Figure 27 a) Pure pectin film exhibited high water vapor permeability and the most severe weight loss. With increasing QAC content, the weight loss rate of the QAC / P composite film group was suppressed, attributed to the enhanced membrane density due to the electrostatic interaction between QAC and pectin molecular chains, thus reducing fruit moisture loss. Although the weight loss rate of the QAC / P group was higher than that of the preservation film group, its firmness maintenance ability was significantly enhanced; the firmness of the 50.0% QAC / P group remained around 1.5 N on day six. On day six of storage, the total bacterial count in the polyethylene preservation film and pure pectin film groups was significantly higher than that in the QAC composite film groups. With increasing QAC content, the growth of microorganisms on the strawberry surface was significantly inhibited, directly slowing down the respiration rate of the strawberries. Figure 26 It can be seen that the 50.0% QAC / P group maintained TSS, indicating that the cationic enhancement system effectively inhibited the consumption of endogenous substances in strawberries and maintained the physiological quality of the fruit. Color value ( Figure 27 The df (color depth) visually reflects the freshness of the strawberries. After 6 days of storage, the brightness (L*) of the polyethylene preservation film group and the pure pectin group decreased significantly, showing obvious signs of spoilage and a dull color. In contrast, the QAC composite film group effectively maintained the original red color (a*) and lower yellowness (b*) of the strawberries. The experimental results indicate that traditional preservation films are ineffective in delaying quality decline in perishable fruits such as strawberries. The QAC / P composite film, with its excellent antibacterial properties, demonstrates significant advantages in maintaining fruit firmness, inhibiting microbial proliferation, and delaying physiological metabolism, making it a promising active packaging material.

Claims

1. A pectin-based composite film based on cotton stalk flour component modification, characterized by, The pectin-based composite film is prepared by graded utilization of cotton stalk components and through electrostatic interaction and hydrogen bond network. The pectin-based composite film includes an LC-NCs composite film (LC / P film) prepared by mixing a lignin-curcumin nanocomposite LC-NCs dispersion with a pectin aqueous solution, and a QAC / P composite film prepared by mixing a cationized cellulose solution (QAC) with a pectin aqueous solution. The contact angle of the LC / P film is maintained above 60°. The tensile strength of both the LC / P film and the QAC composite film is above 45 MPa. The gas barrier capacity is increased by 100%, and the antibacterial effect can reach above 95%.

2. A pectin-based composite film modified with cotton stalk powder as described in claim 1, characterized in that, The method consists of the following steps: 1) The eutectic solvent DES was prepared by heating and stirring, and then sealed and stored for later use; 2) Place cotton stalk powder in a dry beaker, add the eutectic solvent obtained in step 1), stir magnetically and heat, centrifuge the resulting mixed solution while hot to obtain supernatant and bottom solid residue. The supernatant is lignin-DES solution, sealed and stored for later use. The bottom solid residue is washed with anhydrous ethanol and deionized water, dried and pulverized to obtain solid powder for later use. 3) Add curcumin to the supernatant obtained in step 2) and heat and stir to dissolve. While stirring, add deionized water dropwise to the solution. After centrifugation and washing, redisperse in deionized water. After microfluidic treatment, obtain lignin-curcumin nanocomposite LC-NCs dispersion. 4) Add the solid powder obtained in step 2) to the sodium chlorite solution, heat and stir at a constant temperature, wash by centrifugation, and redisperse in deionized water. After ultrasonic, microfluidic and centrifugal treatment, bleached nanocellulose is obtained. 5) Disperse the bleached nanocellulose obtained in step 4) in an alkaline aqueous solution, add the cationic modifier dropwise while maintaining the alkaline conditions of the solution, react at a constant temperature, then adjust the pH value to neutral to terminate the reaction, centrifuge to obtain the precipitate and wash it alternately with anhydrous ethanol and deionized water, dialyze, and finally obtain a uniform and stable cationic cellulose solution QAC. 6) Mix the LC-NCs dispersion and QAC solution obtained in steps 3) and 5) with pectin aqueous solution respectively, stir continuously, add glycerol and stir again to obtain LC / P film solution and QAC / P composite film solution; 7) Spread the LC / P thin film liquid and QAC / P composite film liquid obtained in step 6) onto two glass plates respectively, dry them or let them air dry, and then peel off the films to obtain the LC / P thin film and QAC / P composite film.

3. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 1), the method for preparing the eutectic solvent system is as follows: choline chloride and lactic acid are added to a dry beaker to obtain a mixture, and the mixture is placed in an oil bath at 80°C and magnetically stirred at 80°C until the solid particles completely disappear. The molar ratio of choline chloride to lactic acid is 1:1-1:

6.

4. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 2), the solid-liquid ratio of cotton stalk powder to eutectic solvent is 1:20, the reaction temperature is 130℃, the stirring rate is 150-500 rpm, and the reaction time is 6 h. The centrifugation rate is 8000 rpm for 5 min, and the solid residue must be washed until neutral.

5. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 3), the mass ratio of lignin to curcumin is 20:0-0:20, and it is dispersed in 100.0 mL of deionized water. The high-pressure microfluidic homogenizer is set to an operating pressure of 150 MPa and circulated three times.

6. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 4), weigh 25.0-30.0g of sodium chlorite and dissolve it in 300.0-600mL of deionized water. Add 5.0g of the solid powder from step 2). Adjust the pH of the system to 4-6 with glacial acetic acid. React at 90℃ for 3 hours. Centrifuge at 8000-10000 rpm for 4-6 minutes. After washing, the pH should be neutral. Use an ultrasonic cell disruptor at 60-80% power for 5-8 minutes. Circulate the mixture 2-5 times using a high-pressure microfluidic homogenizer at 150-200 MPa pressure.

7. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 5), the 5.0 g of bleached nanocellulose obtained in step 4) is dispersed in 250.0 mL of sodium hydroxide solution with a mass concentration of 0.015-0.02 g / mL. The cationic modifier is 50.0 mL of 3-chloro-2-hydroxypropyltrimethylammonium chloride solution. The pH of the system is above 10-13. The reaction is carried out continuously at 80℃ for 10-15 h. The centrifugation rate is 8000-10000 rpm and the time is 10-15 min. Dialysis is required for 3 days.

8. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 6), the pectin in the pectin aqueous solution has a pectin mass-volume percentage of 2.0%, the amount of glycerol added is 30% of the pectin mass, the mass of solids in the added LC-NCs dispersion is 0.5%-5.0% of the pectin mass, the amount of cationic cellulose solution added is 0-20.0 mL at a concentration of 50.0 mg / mL, the mixture is stirred for 12 h after adding pectin, and stirred for 1 h after adding glycerol.

9. The method for preparing a pectin-based composite film modified with cotton stalk powder according to claim 1, characterized in that, In step 7), the slurry is spread evenly on the substrate, the substrate size is 25cm×15cm, and the thickness of the slurry is 0.3-0.5cm; the drying conditions are drying at 25-45℃ or natural drying.

10. The application of the pectin-based composite film modified with cotton stalk powder as described in claim 1 in food packaging.